Schools and delinquency in the early 20th century: rethinking the origins of school policing - Burton, Chase S. (The British journal of criminology, 2017)
Schools in the United States are well understood as sites of social control, but the prevailing view is that schools have only become directly and closely linked with justice systems in recent decades. This article argues that much of the recent literature on school policing, the school-to-prison pipeline and related phenomena have overlooked the deeper history of mass education as a fertile grounds for law enforcement activities. The article shows how early on in the life of American mass education, a group of organizations called Coordinating Councils brought schools and law enforcement together to detect, prevent and control delinquency. I conclude that this history troubles dominant explanations of the causes of the close relationship between schools and police